Young Generation's Perceptions of the Farming Profession in Agricultural Regeneration: A Qualitative Case Study: JEL Classification: Q10, Q12, Q18, J24, O13 - Moch Yusoef Agung Ashar; Halbi Halbi; Hamsah Hamsah (Newinera Publisher, 2026)
Farmer regeneration represents a strategic challenge to Indonesia’s food security, including in Polewali Mandar Regency, due to the declining interest of young generations in agricultural professions. This study aims to examine the perceptions of educated youth toward the farming profession and the factors influencing these perceptions. A qualitative approach with a case study design was employed at the Muhammadiyah Institute of Technology and Business of Polewali Mandar. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman model. The findings reveal a dualistic transition of perceptions: farming is regarded as a strategic profession with significant social value, yet it remains stigmatized as a low-prestige occupation. These perceptions are shaped by internal factors (family background, education, and personal experience) and external factors (social media, the role of higher education institutions, and government policy support). The novelty of this study lies in its empirical exploration of the dynamic transition of educated youth perceptions within a region-based agricultural higher education context, which has received limited attention in previous farmer regeneration studies. Practically, the results underscore the importance of agricultural modernization and the strengthened role of higher education and digital media in fostering sustainable farmer regeneration.